The Study on the Relationship Between Resource and Performance- the Case of Accounting Firms in China of MCs Degree - Niu, Lu (2022)
With the establishment and in-depth development of China's socialist market economy system, the accounting firm industry, although having undergone vigorous development, has fallen short of the requirements of China's economic and social development and the level of development of the global accounting industry, while the commitment to fully open up the accounting market to international accounting firms five years after accession to the World Trade Organization and the implementation of new accounting standards that are in line with international standards have further intensified competition in the accounting firm industry and further stimulated the prosperous development of the profession (Xiang, 1998). How to guide the standardized development of large, medium, and small accounting firms by different development positioning, further enhance the comprehensive strength of accounting firms, realize the strategic plan of becoming bigger and stronger, and promote the good and fast development of China's CPA industry has become an important issue for the development of China's accounting firm industry at present and for some time to come.